Find the inverse of y = 2x+1/ x-1

  • Google+ icon
  • LinkedIn icon
  • 777 views

the aim of finsing the inverse is making x the subject. To start we need to multiply both sides by: (x-1), giving us:

y(x-1) = 2x+1

now we need to expand the brackets:

yx - y = 2x+1

now gather all the x components on the same side:

yx-2x = 1+y

now factorise the left hand side:

x(y-2) = 1+y

now make x the subject, giving us:

x = 1+y/ y-2

therefore, the inverse is written in terms of x, which gives us:

f(x)^-1 = 1+y/y-2

Amelia S. GCSE Maths tutor, A Level Maths tutor, GCSE Further Mathema...

About the author

is an online GCSE Maths tutor with MyTutor studying at Exeter University

Still stuck? Get one-to-one help from a personally interviewed subject specialist.

95% of our customers rate us

Browse tutors

We use cookies to improve your site experience. By continuing to use this website, we'll assume that you're OK with this. Dismiss

mtw:mercury1:status:ok